2019
DOI: 10.2147/idr.s217020
|View full text |Cite
|
Sign up to set email alerts
|

<p>Potential role of the antimicrobial peptide <em>Tachyplesin III</em> against multidrug-resistant <em>P. aeruginosa</em> and <em>A. baumannii</em> coinfection in an animal model</p>

Abstract: BackgroundTachyplesin III, an antimicrobial peptide (AMP), provides protection against multidrug-resistant (MDR) bacterial infections and shows cytotoxicity to mammalian cells. Mixed bacterial infections, of which P. aeruginosa plus A. baumannii is the most common and dangerous combination, are critical contributors to the morbidity and mortality of long-term in-hospital respiratory medicine patients. Therefore, the development of effective therapeutic approaches to mixed bacterial infections is urgently neede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The peptide enhances the phagocytic function in mouse alveolar macrophages when tested in vitro, which hints at its candidacy as a clinical drug for the treatment of respiratory tract and lung infections. 94 Murepavadin (POL7080) is peptidomimetic based on the cationic AMP protegrin 1. It has passed the phase 2 clinical trials for the treatment of ventilator-associated bacterial pneumonia caused by P. aeruginosa (NCT02096328).…”
Section: Amps As Therapeutic Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide enhances the phagocytic function in mouse alveolar macrophages when tested in vitro, which hints at its candidacy as a clinical drug for the treatment of respiratory tract and lung infections. 94 Murepavadin (POL7080) is peptidomimetic based on the cationic AMP protegrin 1. It has passed the phase 2 clinical trials for the treatment of ventilator-associated bacterial pneumonia caused by P. aeruginosa (NCT02096328).…”
Section: Amps As Therapeutic Agentsmentioning
confidence: 99%
“…Moreover, Tachyplesin III can also decrease the levels of pro‐inflammatory cytokines in the serum, including IL‐1β, IL‐6, and TNF‐α. The peptide enhances the phagocytic function in mouse alveolar macrophages when tested in vitro, which hints at its candidacy as a clinical drug for the treatment of respiratory tract and lung infections 94 . Murepavadin (POL7080) is peptidomimetic based on the cationic AMP protegrin 1.…”
Section: The Structure Classification and Mechanism Of Ampsmentioning
confidence: 99%
“…There is speculation that the secondary and tertiary structures of these molecules determine their lethality, but interestingly, the two AMPs noted differ in both secondary structure and hydrophilic/hydrophobic arrangements [50]. An in vivo study examining tachyplesin III's role in combating concomitant P. aeruginosa and A. baumannii lung infections found that pre-treatment with the peptide reduced inflammation, bacterial burden, and lung damage by increasing phagocytosis and reducing cytokine release in mice [51]. If funding can be secured, AMPs may be the future of antimicrobial treatment strategies.…”
Section: Other Therapeutic Approachesmentioning
confidence: 99%
“…Only a few AMPs have been tested in lung polymicrobial infections. One of these peptides is the Tachyplesin III, a β-sheet peptide from the hemocytes of the horseshoe crab ( Tachypleus tridentatus ), which has been tested in bacterial co-infection pneumonia [ 55 ]. As compared to mono-bacterial infection, the intranasal co-infection of mice with MDR P. aeruginosa and A. baumannii caused a more serious disease, with increased pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and chemokines (MCP-1/MIP-2) and reduced survival.…”
Section: Bacteria–bacteria Mixed Infectionsmentioning
confidence: 99%